MATHEMATICS IN THE EMERGENCY PUBLIC ACTIVITY RESTRICTIONS (PPKM): HOW ABOUT SELF-CONFIDENCY OF THE STUDENTS? - Widya Ayu Pangestika; Adi Nurcahyo (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2021)
The aims of this study to analyze student’s self-confidence in learning mathematics during PPKM. This is descriptive qualitative research, where there are three students who take part in PCGP organized by Universitas Muhammadiyah Surakarta. The auxiliary instruments consist of self-confidence questionnaires, interview guidelines, and field notes. Data collected by distribute questionnaires to research subjects, interviews with parents and teachers, and direct observations. Triangulation of sources and methods used to validate the obtained data. It showed that learning during PPKM did not have a significant effect on student’s self-confidence. The percentage of student's self-confidence in learning mathematics during PPKM was 85%, which was quite good in accordance with the field conditions. Environment become vital role which was very necessary during online learning to assist students in learning.